Potential Indonesian Rice Husk for Wastewater Treatment Agricultural Waste Preparation and Dye Removal Application - Palapa, Neza Rahayu; Amri; Yuliza Hanifah (Indonesian Journal of Environmental Management and Sustainability, 2023)
This study used a novel method to transform rice husk waste into a highly effective and specific adsorbent for several dyes, including malachite green, direct yellow, congo red, and rodhamine B. The rice husk was analyzed and used for the purpose of eliminating these colors from water-based solutions. The adsorbent exhibited excellent heat stability, and the sample retained the functional groups of lignin. The parameters pertaining to kinetics were also examined. The adsorption exhibited a time-dependent rise and reached its peak after 100 minutes. In the kinetics tests, the most suitable model to characterize the behavior was found to be the pseudo-first order, with a regression value near to one. The rice husk shown significant potential and selectivity in the removal of malachite green and rodhamine B, particularly in the presence of direct yellow and congo red, from aqueous solutions.